PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA GOOGLE EARTH PADA MATA PELAJARAN IPAS KELAS V UNTUK MENINGKATKAN KETERAMPILAN SPASIAL - Krisdianto, Indun; Jupriadi; Sudarmiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of the study is to determine the improvement of the spatial appearance of IPAS class V Elementary School, the Classroom Action Research Approach (PTK) was chosen in this research to observe the development of spatial abilities of students in class V. The focus of the research is directed at improving the aspects of visualization, perception, orientation, and spatial relations in IPAS subjects. Learning transformation is carried out by applying the Problem Based Learning syntax supported by the use of Google Earth technology-based media requires a contextual approach and is able to develop critical thinking skills, conventional learning is less able to facilitate the visualization of spatial concepts in real terms. The limitations of conventional media in presenting landscapes and locations in three dimensions (3D) are obstacles in the development of students' Spatial Visualization and Spatial Orientation skills. The implementation of the Project Based Learning model with Google Earth media has implications for improving spatial skills. With the results of Cycle I from 78.3 Cycle II to 83.7. This increase is in line with the percentage of completeness or achievement which also increased from 78.3% to 83.7%. This improvement in the quality of spatial skills is also reflected in the distribution of individual grades of students with the highest scores experiencing an increase in the upper limit of students' abilities from a score of 88 to 94, this confirms that the Project Based Learning model with Google Earth media is effective in comprehensively understanding aspects of perception, visualization, orientation, and spatial relations in V SD class students.